2010
DOI: 10.1021/jp105949z
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stability and Electronic Properties of InAs Nanowires and Nanotubes: Effects of Surface and Size

Abstract: The surface and size effects on the structural stability and electronic properties of InAs one-dimensional nanostructures are investigated by first-principles calculations within density functional theory. No matter what the diameters, the nanowires are more energetically favorable than the nanotubes due to the preferable sp3 hybridization for In and As atoms in the InAs nanostructures. The formation energies of these nanostructures satisfy a linear dependence relationship with the surface atom ratio. The calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…After structural optimization, both pure ZnO and GaN ) 00 1 1 ( _ and ) 0 2 11 ( _ nanofilms with given 8 and 10 layers exhibit slightly inward and outward motions of Zn (Ga) and O (N) at the surfaces, which has also been reported in previous studies [36,37]. The optimized supercell sizes For further examining the structural stability of ZnO/GaN heterostructured nanofilms, the formation energy has been calculated according to the following equation [38,39] , In the former, it increases monotonically, whereas it shows an oscillating increase in the latter.…”
Section: Structural Stabilitymentioning
confidence: 64%
See 1 more Smart Citation
“…After structural optimization, both pure ZnO and GaN ) 00 1 1 ( _ and ) 0 2 11 ( _ nanofilms with given 8 and 10 layers exhibit slightly inward and outward motions of Zn (Ga) and O (N) at the surfaces, which has also been reported in previous studies [36,37]. The optimized supercell sizes For further examining the structural stability of ZnO/GaN heterostructured nanofilms, the formation energy has been calculated according to the following equation [38,39] , In the former, it increases monotonically, whereas it shows an oscillating increase in the latter.…”
Section: Structural Stabilitymentioning
confidence: 64%
“…Thus, the charge distributions of VBM and CBM are great significant for understanding the potential applications in photocatalytic field. For the low-dimensional nanostructures, size effects on electronic properties become remarkable and cannot be neglected [38,[42][43][44]. Consequently, this raises a question: what are the relationships between the optical properties and the sizes of ZnO/GaN heterostructured nanofilms?…”
Section: Spatial Charge Distribution and Optical Propertiesmentioning
confidence: 99%
“…7 Successful realization of these applications depends on the control of their structures and fundamental electronic properties. Both experimental [2][3][4]8 and theoretical studies [9][10][11][12] have been carried out and devoted to finding some feasible methods to control the electronic properties of InAs and other semiconductor nanowires. It has been found that the electronic structures of nanowires can be tailored by the nanowire size and morphology, doping, and surface functionalization.…”
Section: Tailoring Electronic Properties Of Inas Nanowires By Surfacementioning
confidence: 99%
“…Many experimental investigations for III-V NWs have been performed but diameters typically are much larger than the 10 nanometer upper limit required for advanced nanoelectronics geometries [24][25][26]. Theoretical studies of III-V NWs have typically considered unterminated NWs, idealized surface terminations using pseudo-hydrogen, or considering only a single atomic species for surface passivation [27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%